Novel COL6A2 mutation in a case of limb girdle muscular dystrophy phenotype with autosomal recessive inheritance. Issue 5 (13th July 2016) - Mitsui, Jun; Ishiura, Hiroyuki; Yoshimura, Jun; Doi, Koichiro; Morishita, Shinichi; Shoji, Hiroshi; Arimori, Yojiro; Matsumoto, Takafumi; Shimizu, Jun; Tsuji, Shoji
Abstract: We describe sibling cases presenting with long‐standing, slowly progressive proximal muscle weakness without joint contractures or hyperlaxity. Whole‐exome sequence analysis showed compound heterozygous mutations including a novel stop codon mutation of p.*1020Yext*86 (c.3060G > C) in COL6A2 as the causative mutations, establishing the diagnosis of COL6A2 ‐related myopathy presenting with limb girdle muscular dystrophy phenotype with autosomal recessive inheritance. Collagen VI‐related myopathies should be considered in patients with early childhood‐onset, slowly progressive proximal weakness even without joint contractures.